2012
DOI: 10.1016/j.exphem.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Mice heterozygous for CREB binding protein are hypersensitive to γ-radiation and invariably develop myelodysplastic/myeloproliferative neoplasm

Abstract: Myelodysplastic syndrome (MDS) is a complex family of pre-leukemic diseases in which hematopoietic stem cell defects lead to abnormal differentiation in one or more blood lineages. Disease progression is associated with increasing genomic instability and a large proportion of patients go on to develop acute myeloid leukemia. Primarily a disease of the elderly, it can also develop following chemotherapy. We have previously reported that CREB binding protein (Crebbp) heterozygous mice have an increased incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
2
28
1
Order By: Relevance
“…CREB overexpression was found in many solid tumor types like non-small lung carcinoma (NSCLC), glioblastoma, mammary carcinoma, melanoma and diffuse malignant mesothelioma when compared to adjacent normal tissues [8, 10, 1422] as well as in hematopoietic malignancies [2326]. This was accompanied by enhanced cell proliferation, reduced sensitivity to undergo apoptosis, increased angiogenesis and radiation-induced differentiation [27].…”
Section: Role Of Creb In the Tumor Developmentmentioning
confidence: 99%
“…CREB overexpression was found in many solid tumor types like non-small lung carcinoma (NSCLC), glioblastoma, mammary carcinoma, melanoma and diffuse malignant mesothelioma when compared to adjacent normal tissues [8, 10, 1422] as well as in hematopoietic malignancies [2326]. This was accompanied by enhanced cell proliferation, reduced sensitivity to undergo apoptosis, increased angiogenesis and radiation-induced differentiation [27].…”
Section: Role Of Creb In the Tumor Developmentmentioning
confidence: 99%
“…Naïve Crebbp 1/2 mice show HSC defects, 45 BM hypercellularity, splenomegaly, and myelodysplasia with hypersegmented granulocytes and pseudoPelger-Huet anomalies in the PB and abnormal megakaryocytes (ie, hyperlobulation and naked nuclei) in the BM. 30 There is no cytopenia. Instead, these mice show PB granulocytosis and excessive myelopoiesis in marrow and spleen.…”
Section: Myelodysplastic Features and Pitfalls Illustratedmentioning
confidence: 99%
“…Instead, these mice show PB granulocytosis and excessive myelopoiesis in marrow and spleen. 30 The hematologic syndrome observed in naïve Crebbp 1/2 mice was therefore classified as an MDS/MPN overlap disease. 40,42,46,47 The BM microenvironment contributes to the myeloproliferative component of the hematologic disease observed in Crebbp 1/2 mice, in part through the altered production levels of KITL and MMP9.…”
Section: Myelodysplastic Features and Pitfalls Illustratedmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic instability is associated with progression of the disease so that a part of patients develops AML. It has been reported that an increased incidence of haematological malignancies occurs in CREBBP heterozygous mice and other authors have shown that CREBBP is one of the genes altered by chromosomal translocations in patients suffering from therapy-related myelodysplastic syndrome [69]. Moreover, it has been demonstrated that CREBBP(+/-) mice invariably develop myelodysplastic/myeloproli-ferative neoplasm within 9-12 months of age.…”
Section: Acute Myeloid Leukaemiamentioning
confidence: 93%